Body posture vs body composition in adolescent girls - Burdukiewicz, Anna; Pietraszewska, Jadwiga; Andrzejewska, Justyna; Piojda, Tomasz; Stachoń, Aleksandra (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The puberty is distinguished by significant changes in the morphological and functional characteristics of the organism’ systems. It is also a critical phase during forming of body posture. The aim of the paper is to examine the variability of development of postural characteristics and body composition of girls aged 13-15 years. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and Method. There were used the longitudinal measurements of 91 girls attending a public high school in Wroclaw, namely body weight and height, which were then used to calculate BMI. The body composition was assessed by bioelectrical impedance analysis (apparatus BIA 101S produced by Akern, software Bodygram 1.31). In the analysis, the following features were considered: body cell mass, extracellular mass, fat mass, lean body mass. On the basis of the absolute values two ratios were calculated: body cell mass / extracellular mass and lean body/fat. The posture assessment was carried out using a computer coupled with Posturometr S. The calculations were performed using Statistica 10 package. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results and conclusions. There has been noted an increase in the massiveness of body build assessed by BMI and larger body cell mass in relation to the extracellular mass. The relation in lean body mass to the fat was markedly reduced, which is associated with the shape typical for female proportions of body composition. Growing postural characteristics such as shoulder height, infrascapular height and iliospinale superior posterior height is similar to the changes in body height. With age, the slope of sacral part of spine decreases and increases the angle of inclination of the thoraco-lumbar part. In the following comparisons, increasing frequency of kyphotic silhouettes (subtype II), balanced (all subtypes) and lordotic (subtype II) were observed. Moreover, there was a tendency to increasing number of persons with very good body posture. At the age of 14 years, there was noted a transient increase in the frequency of defective and bad posture.